ROLE OF ANTI-VASCULAR ENDOTHELIAL GROWTH FACTORS IN THE TREATMENT OF CHRONIC AND RECURRENT CENTRAL SEROUS CHORIORETINOPATHY - S.M, MADAKI; D.K, SONJOY; HABIB S.G, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
The study evaluate the role of anti-vascular endothelial growth factors (Anti-Vegf) in the treatment of chronic central serous chorioretinopathy (CSCR). It was a hospital base prospective interventional non randomized study. Patients with history of chronic CSCR lasting for more than 3 months were treated with intravitreal Bevacizumab 1.25mg or Ranibizumab 0.5mg after measurement of best corrected visual acuity (BCVA), intraocular pressure (IOP), dilated fundus examination and central macular thickness using OCT. Patient shows complete resolution of subretinal fluid and restoration of visual acuity to normal after 3months. In conclusion, intravitreal injection of anti-vegf results in restoration of normal vision in patient with CSCR.